Advancing universal health coverage in South Asian cities: a framework. (29th November 2018) - Adams, Alayne M; Nambiar, Devaki; Siddiqi, Sameen; Alam, Bushra Binte; Reddy, Srinath
Abstract : Alayne Adams and colleagues propose a framework that emphasises actions on urban health governance and the social determinants of health to achieve universal health coverage in South Asian cities